Individual Educational Trajectories in Higher Education Institution - Global Challenges for Regions - Parnikova Galina; Antsupova Svetlana (E3S Web of Conferences, 2021)
The need to introduce individualization of education in the universities of Yakutia is dictated by the need to find optimum solutions for preserving human capital in the northern territories, attracting applicants to regional universities and the labor market’s need for competitive specialists from the local population. The purpose of the study is to develop innovative approaches to the educational process in regional universities in the context of global challenges. Research methods: analysis and processing of data from an array of theoretical sources and educational practice; modeling. Scientific novelty of the research: a personality-oriented model of education at the university has been built, taking into account the regional specifics and factors affecting the formation of individual educational trajectories of students.